The Relationship between Coping Strategies and Quality of Life in Patients with Heart Failure - Putri Intan Miladiana; Beti Kristinawati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Heart failure is one of the most common cardiovascular diseases, causing high mortality and morbidity worldwide. Heart failure is a chronic disease that causes functional damage to the heart due to many symptoms that affect quality of life. The aim of this study was to clarify the relationship between coping strategies and quality of life in heart failure patients. This type of research is a quantitative study with a cross-sectional approach. This research was conducted on heart failure patients at the Cardiac Polyclinic at Sebelas Maret University Hospital in March-April 2023. The population of this study was all heart failure patients at the Cardiac Polyclinic at Sebelas Maret University Hospital as many as 1.114 patients. The sampling technique in this study was purposive sampling with a total sample of 294 patients. Data collection in this study used the Brief Cope Inventory questionnaire to measure coping strategies and the Minnesota Living Heart Failure Questionnaire (MLHFQ) to measure the quality of life in heart failure patients. Data analysis with pearson product moment correlation test. The results showed that there was a relationship between coping strategies and quality of life in heart failure patients (p-value 0.000) with a correlation coefficient (r) = 0.625, there was a very strong correlation between the two variables. It is recommended for health workers to educate, support, and motivate patients with heart failure who are undergoing routine treatment to pay attention to self-coping and improve the quality of life, and it is recommended that the patient's family provide support and treatment assistance to patients in carrying out treatment in order to improve the patient's quality of life. Keyword: Coping Strategies, Heart Failure, Quality of Life